How Drawing to Distract Improves Mood in Children - Drake, Jennifer E. (Frontiers in Psychology, 2021)
Previous research has shown that drawing improves short-term mood in children when used to distract from rather than express negative thoughts and feelings. The current study sought to examine (a) how drawing might elevate mood in children ages 6 to 12 by examining the role played by absorption, enjoyment, and competence as well as entering an imaginary world; and (b) whether children spontaneously use drawing to distract from a sad mood. Across three studies, children were asked to think of a disappointing event. After the sad mood induction, they drew for 5 min. Mood was measured before and after the mood induction and after drawing. Three main findings emerged. First, drawing to distract led to greater absorption and enjoyment than did drawing to express. Second, children’s mood improved equally when drawing imaginary and real scenes showing that the key ingredient is that the content of the drawings be distracting in nature. Third, drawing improved mood even when children were given no instructions on the content of their drawings and children were more likely to use drawing as a way to distract themselves from a sad mood. These studies help to define the characteristics of drawing activities that foster mood improvement in children and highlight the important role of the arts in emotion regulation.